2010
DOI: 10.1080/07315724.2010.10719823
|View full text |Cite
|
Sign up to set email alerts
|

Renal Zinc Clearance/Glomerular Filtration Rate Ratio as an Indicator of Marginal Zinc Deficiency Associated with Iron Deficiency in Childhood

Abstract: R(ClZn)/GFR ratio was a reliable indicator for reduction in urinary zinc excretion; it estimated the marginal zinc deficiency associated with iron deficiency. The R(ClZn)/GFR ratio can be calculated using one sample of blood and urine; thus it could serve as an alternative indicator of marginal zinc deficiency, especially in routine health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…In the study by Bains et al [5], Zn deficiency was detected in 17.9% of children aged 6 months-5 years, and rates of low Fe and ferritin level were 84.6% and 71.8% among children with Zn deficiency, respectively. In the studies of Tural et al [8] and Kelkitli et al [9] from Turkey, Zn deficiency has been frequently detected in patients with Fe deficiency. In the study by Erdoğan et al [10], serum Zn level was markedly lower in patients with Fe deficiency anemia than in controls.…”
Section: Discussionmentioning
confidence: 98%
“…In the study by Bains et al [5], Zn deficiency was detected in 17.9% of children aged 6 months-5 years, and rates of low Fe and ferritin level were 84.6% and 71.8% among children with Zn deficiency, respectively. In the studies of Tural et al [8] and Kelkitli et al [9] from Turkey, Zn deficiency has been frequently detected in patients with Fe deficiency. In the study by Erdoğan et al [10], serum Zn level was markedly lower in patients with Fe deficiency anemia than in controls.…”
Section: Discussionmentioning
confidence: 98%
“…Motadi et al [7] revealed the rate of association of Fe and Zn deficiencies as 2% among preschool-age children. Tural et al [8] noted that there was a strict relationship between Fe and Zn, attributing this relationship to the fact that Zn is a cofactor for several enzymes involved in Fe metabolism. Kelkitli et al [9] found markedly low serum Zn level in patients with Fe deficiency anemia when compared with controls, suggesting that Zn levels should be assessed in patients with Fe deficiency anemia.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 26 studies measured urinary zinc in infants and children aged 0 to 9 years. [48][49][50][51]54,57,60,[62][63][64][67][68][69][70][71]74,[76][77][78][79][82][83][84][85][86][87] Of these, 14 provided data from children aged 0 to 3 years [48][49][50]54,57,60,67,71,73,74,77,84,86,87 and 13 provided data from children aged 4.5 to 9 years. 48,51,[62][63][64][68][69][70]76,79,82,…”
Section: Data Synthesismentioning
confidence: 99%
“…Tables S1 and S3 in the Supporting Information provide descriptions of these studies, with Table S1 detailing studies excluded from the metaanalyses and Table S3 detailing studies included in the meta-analyses. Urinary zinc was measured by atomic absorption spectrometry, 48,49,51,54,60,[62][63][64]68,69,71,74,[76][77][78][79]82,84,86,87 a colorimetric method, 50,67 inductively coupled plasma-atomic emission spectrophotometry, 85 inductively coupled plasma mass spectrometry, 70 and liquid chromatography. 83 Three studies assessed zinc excretion from spot urine samples.…”
Section: Data Synthesismentioning
confidence: 99%